Recommendations for the use of Lyme disease vaccine: recommendations of the Advisory Committee on Immunization Practices (ACIP) [corrected] [published erratum appears in MMWR MORB MORTAL WKLY REP 1999 Sep 24; 48(37): 833]. (MMWR: Morbidity & Mortality Weekly Report, 1999)
This report provides recommendations for use of a newly developed recombinant outer-surface protein A (rOspA) Lyme disease vaccine (LYMErix,[TM] SmithKline Beecham Pharmaceuticals) for persons aged 15-70 years in the United States. The purpose of these recommendations is to provide health-care providers, public health authorities, and the public with guidance regarding the risk for acquiring Lyme disease and the role of vaccination as an adjunct to preventing Lyme disease. The Advisory Committee on Immunization Practices recommends that decisions regarding vaccine use be made on the basis of assessment of individual risk, taking into account both geographic risk and a person's activities and behaviors relating to tick exposure.